Comparative study between apocynin and protocatechuic acid regarding antioxidant capacity and vascular effects - Graton, Murilo E.; Ferreira, Bruno H. S. H.; Troiano, Jéssica A.; Potje, Simone R.; Vale, Gabriel T.; Nakamune, Ana Cláudia M. S.; Tirapelli, Carlos R.; Miller, Francis J.; Ximenes, Valdecir F.; Antoniali, Cristina (Frontiers in Physiology, 2022)
Reactive oxygen species (ROS) derived from NOX enzymes activity play an important role in the development of cardiovascular diseases. Compounds able to decrease oxidative stress damage are potential candidates as drugs and/or supplements for hypertension treatment. Here, we aimed to compare in vitro ROS scavenging potency, effective NOX inhibition and effects on vascular reactivity of apocynin to another phenolic compound, protocatechuic acid, in vascular cells from spontaneously hypertensive rat (SHR), where redox signaling is altered and contributes to the development and/or maintenance of hypertension. We evaluated the in vitro antioxidant capacity and free radical scavenging capacity of both phenolic compounds. Moreover, we investigated the effect of both compounds on lipid peroxidation, lucigenin chemiluminescence, nitric oxide (NO•) levels and ROS concentration in vascular cells of SHR or human umbilical vein endothelial cell (HUVEC). Apocynin and protocatechuic acid presented antioxidant capacity and ability as free radical scavengers, decreased thiobarbituric acid reactive substances (TBARS) in aortic cells from SHR, and increased NO• concentration in isolated HUVEC. Both compounds were able to reduce lucigenin chemiluminescence and increased the potency of acetylcholine in aorta of SHR. However, in SHR aortas, only apocynin diminished the contraction induced by phenylephrine. In conclusion, these results strongly reinforce the potential application of substances such as apocynin and protocatechuic acid that combine abilities as scavenging and/or prevention of ROS generation, establishment of NO bioactivity and modulation of vascular reactivity. Due to its phytochemical origin and low toxicity, its potential therapeutic use in vascular diseases should be considered.